2020
DOI: 10.1002/adma.202002578
|View full text |Cite
|
Sign up to set email alerts
|

Effective Modulation of CNS Inhibitory Microenvironment using Bioinspired Hybrid‐Nanoscaffold‐Based Therapeutic Interventions

Abstract: Central nervous system (CNS) injuries are often debilitating, and most currently have no cure. This is due to the formation of a neuroinhibitory microenvironment at injury sites, which includes neuroinflammatory signaling and non‐permissive extracellular matrix (ECM) components. To address this challenge, a viscous interfacial self‐assembly approach, to generate a bioinspired hybrid 3D porous nanoscaffold platform for delivering anti‐inflammatory molecules and establish a favorable 3D‐ECM environment for the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 62 publications
(45 reference statements)
1
23
0
Order By: Relevance
“…Addressing the above problems, one promising approach is to use scaffold materials to generate favorable microenvironments during stem cell implantation (13)(14)(15)(16). These scaffolds can help generate three-dimensional (3D) stem cell assembly, mitigate local inflammation, and establish favorable cell-extracellular matrix (ECM) interactions, typically mediated through focal adhesion kinase (FAK) signaling, which critically regulates neurogenesis and axon elongation (17)(18)(19)(20)(21)(22). Nevertheless, a few challenges have been reported in these scaffold-based approaches.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Addressing the above problems, one promising approach is to use scaffold materials to generate favorable microenvironments during stem cell implantation (13)(14)(15)(16). These scaffolds can help generate three-dimensional (3D) stem cell assembly, mitigate local inflammation, and establish favorable cell-extracellular matrix (ECM) interactions, typically mediated through focal adhesion kinase (FAK) signaling, which critically regulates neurogenesis and axon elongation (17)(18)(19)(20)(21)(22). Nevertheless, a few challenges have been reported in these scaffold-based approaches.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, we can better control the formation of spheroids and their differentiation into functional neurons in vitro and in vivo, resulting in improved therapeutic outcomes in a spinal cord injury (SCI) animal model. To accomplish these goals, manganese dioxide nanosheet was used as an ideal nanomaterial for spheroid formation due to their high drug loading, redox-mediated biodegradation, magnetic resonance imaging (MRI)-active degradation products, and biocompatibility (20,21,40,41). Although several other nanomaterials (e.g., graphene nanosheets, gold nanowires, and carbon nanotubes) have been applied for 3D stem cell cultures, most of them are intrinsically nonbiodegradable, do not facilitate the assembly process, and have limited biocompatibility for in vivo applications (14,15,18,22,(42)(43)(44)(45).…”
Section: Introductionmentioning
confidence: 99%
“…Serotonin (5-HT) axons are motor nerve fibers that descends to the ventral gray matter of the spinal cord. They regulate spinal network activity after SCI, thus accelerating recovery of motor function [ 8 , 56 ]. Further analysis was conducted to explore whether 5-HT axons had extended into the injured site along with GFAP.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, the tissue impairs transmission of electrical signal in living nerve cells in the lesion site [ 7 ]. Critically, this damages electric connections across the injured spinal cord, eventually disrupting neural circuits [ 8 ]. Therefore, formation of cystic cavities and glial fibrosis significantly limits SCI repair [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, biomaterial scaffolds hold considerable promise with respect to enhancing the efficacy of SCI repair [16][17][18][19], and hydrogels rank among the most ideal carriers for stem cell delivery. Previous studies have shown that hydrogels, including hyaluronic acid (HA) [20][21][22], poly(lactic-co-glycolic acid) (PLGA) [23,24], poly (2hydroxyethylmethacrylate) (HEMA) [25,26], nanofiber [27][28][29], and self-assembled peptide hydrogels [30][31][32], can be engineered to mimic the architecture of the lost ECM in the spinal cord and can structurally support cell migration and axonal regrowth. Our previous study reported a Pluronic F-127 (PF-127)-based thermo-sensitive hydrogel for enhancing SCI treatment [33].…”
Section: Introductionmentioning
confidence: 99%